Public sector strikes in Iceland - Aðalsteinsson, Gylfi Dalmann (Stjórnsýslustofnun, 2015)
Strikes are a key tool for workers to achieve their demands against their counterparties. The right to strike for workers in the private sector was incorporated in law in 1938. The situation was different for public sector employees in the 20th century regarding the right to strike, salaries were decided by law. According to law from 1915 public sector employees were not allowed to go on strike. In 1976 civil servants were granted the right to strike regarding the main collective agreement and majority of public sector employees were authorized by law the right to strikes in 1986. This study presents strikes of the public sector employees i.e. employees of the state and local government from the year 1977 and shed light on the main reasons for the strike activities in the public sector. Since 1977 there have been 1.974.699 days lost due to industrial conflict in Iceland, whereof 932.102 or 47,7% are because of public sector strikes. Therefore public sector employees in Iceland, who are only 20% of the active labour market constitutes for almost half of all days lost due to strikes in Iceland. To get a comparison between strike frequency between the public and private sector strike volume was calculated. The strike volume shows the number of lost working days per 1,000 employees. The paper brings into light the main explanatory factors of the high strike frequency among public sector employees and discusses ways that can reduce the industrial conflict in the public sector. Some relate to the laws and regulations, other concern the industrial relations between the parties as well as collective bargaining arrangements. Verkföll eru eitt helsta tæki launþega til að ná fram kröfum gagnvart viðsemjendum sínum. Hér á landi var þessi réttur launþega á almennum vinnumarkaði lögfestur árið 1938. Staða opinberra starfsmanna fram eftir 20. öldinni var frábrugðin stöðu launþega á almennum vinnumarkaði hvað samnings- og verkfallsrétt varðaði. Launakjör voru ákvörðuð með lögum. Verkfallsréttur opinberra starfsmanna var ...